Male Stress Urinary Incontinence: A Review of Surgical Treatment Options and Outcomes. (8th May 2012) - Trost, Landon; Elliott, Daniel S.
Abstract : Introduction and Objective . Iatrogenic male stress urinary incontinence (SUI) affects a percentage of men undergoing urologic procedures with a significant impact on quality of life. The treatment of male SUI has evolved significantly with multiple current options for treatment available. The current paper discusses preoperative evaluation of male SUI, available surgical options with reported outcomes, and postoperative complication management. Methods . A pubMed review of available literature was performed and summarized on articles reporting outcomes of placement of the artificial urinary sphincter (AUS) or male slings including the bone anchored sling (BAS), retrourethral transobturator sling (RTS), adjustable retropubic sling (ARS), and quadratic sling. Results . Reported rates of success (variably defined) for BAS, RTS, ARS, and AUS are 36–67%, 9–79%, 13–100%, and 59–91% respectively. Complications reported include infection, erosion, retention, explantation, and transient pain. Male slings are more commonly performed in cases of low-to-moderate SUI with decreasing success with higher degrees of preoperative incontinence. Conclusions . An increasing number of options continue to be developed for the management of male SUI. While the AUS remains the gold-standard therapy for SUI, male sling placement is a proven viable alternative therapy for low-to-moderate SUI.